2020
DOI: 10.1038/s41467-020-18283-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of single ZTP riboswitches reveals a complex and kinetically controlled decision landscape

Abstract: RNAs begin to fold and function during transcription. Riboswitches undergo cotranscriptional switching in the context of transcription elongation, RNA folding, and ligand binding. To investigate how these processes jointly modulate the function of the folate stress-sensing Fusobacterium ulcerans ZTP riboswitch, we apply a single-molecule vectorial folding (VF) assay in which an engineered superhelicase Rep-X sequentially releases fluorescently labeled riboswitch RNA from a heteroduplex in a 5′-to-3′ direction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…While studies have extensively characterized the structures of riboswitch ADs (22)(23)(24)(25)(26), current research is only just beginning to understand how structural features induced by ligand binding in the AD can alter the EP structure and determine gene expression outcomes during transcription (27)(28)(29)(30)(31)(32)(33). Extensive progress has come from the study of transcriptional 'ON' riboswitches that contain an overlap in sequence between the AD and EP that lends to mutually exclusive folds of these two domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have extensively characterized the structures of riboswitch ADs (22)(23)(24)(25)(26), current research is only just beginning to understand how structural features induced by ligand binding in the AD can alter the EP structure and determine gene expression outcomes during transcription (27)(28)(29)(30)(31)(32)(33). Extensive progress has come from the study of transcriptional 'ON' riboswitches that contain an overlap in sequence between the AD and EP that lends to mutually exclusive folds of these two domains.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive progress has come from the study of transcriptional 'ON' riboswitches that contain an overlap in sequence between the AD and EP that lends to mutually exclusive folds of these two domains. In these cases, studies have shown that ligand-binding stabilizes the AD fold, which prevents the EP from forming a terminator hairpin (27)(28)(29)34). On the other hand, when a ligand is not bound, EP folding disrupts the AD structure through RNA strand displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule Förster resonance energy transfer (smFRET) assays have been invaluable to study the dynamics of single RNA molecules by allowing the monitoring of specific structural changes under equilibrium or nonequilibrium conditions ( 12 , 13 ). However, since bacterial and eukaryotic RNAP active sites do not accommodate fluorescent nucleotides ( 14 , 15 ), studies attempting to monitor the folding of nascent transcripts have been restricted to using synthetic constructs or nonnative systems ( 12 , 16 18 ). Although such systems provided important insights about transcriptional mechanisms, they do not use the native RNAP and hence cannot establish the influence of key parameters, such as RNAP pausing, elongation rate, and nascent RNA–protein interactions that are specific to native complexes.…”
mentioning
confidence: 99%
“…Various methods have been used to understand co-transcriptional folding of RNA including single-molecule fluorescence resonance energy transfer (smFRET) [17][18][19] ; optical-trapping 6 ; and selective 2′-hydroxyl acylation analyzed by primer extension sequencing (SHAPE-seq) [20][21][22] . Applying SHAPE-seq to the B. cereus fluoride riboswitch with RNAP stalled at each nucleotide position in particular revealed ligand-dependent delays in terminator formation and identified the point at which the outcome of transcription is determined 20 .…”
Section: Introductionmentioning
confidence: 99%